2019
DOI: 10.3348/kjr.2018.0729
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Blood Flow Quantified by Low-Dose Dynamic CT Myocardial Perfusion Imaging Is Associated with Peak Troponin Level and Impaired Left Ventricle Function in Patients with ST-Elevated Myocardial Infarction

Abstract: Objective To investigate the association of myocardial blood flow (MBF) quantified by dynamic computed tomography (CT) myocardial perfusion imaging (MPI) with troponin level and left ventricle (LV) function in patients with ST-segment elevated myocardial infarction (STEMI). Materials and Methods Thirty-five STEMI patients who successfully had undergone reperfusion treatment within 1 week of their infarction were consecutively enrolled. All patients were referred for dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
1
4
0
2
Order By: Relevance
“…This suggests less myocardial injury in patients with MINOCA compared to patients with MI-CAD, whereas the indicators of myocardial blood flow (MBF stress, MBF rest) were lower in MI-CAD patients. Thus, the larger the area of myocardial injury, the greater the decrease in MBF and MFR [28], as demonstrated by our team previously [29].…”
Section: Relationship Between Indicators Of Prothrombotic Activity In...supporting
confidence: 74%
“…This suggests less myocardial injury in patients with MINOCA compared to patients with MI-CAD, whereas the indicators of myocardial blood flow (MBF stress, MBF rest) were lower in MI-CAD patients. Thus, the larger the area of myocardial injury, the greater the decrease in MBF and MFR [28], as demonstrated by our team previously [29].…”
Section: Relationship Between Indicators Of Prothrombotic Activity In...supporting
confidence: 74%
“…https://doi.org/10.3348/kjr.2020.0249 kjronline.org 4). With the recent introduction of third generation dual source CT (DSCT), it is now technically feasible to perform dynamic CT-MPI at lower radiation doses compared to previous CT scanners (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Nakauchi et al quantified MBF parameters using dynamic CTP with deconvolution analysis in patients after AMI and measured significant differences in tissue blood flow and blood volume between infarcted and non-infarcted myocardial territories (mean MBF: 51.96 versus 108.84 mL/ 100 g/min, P < 0.01) [64]. In patients with ST-segment elevation myocardial infarction and successful revascularization Pan et al found that MBF derived from dynamic CTP significantly and inversely correlated with peak Troponin T levels (r 5 À0.682, P < 0.001) and left ventricular function at 6 months (r 5 0.585, P 5 0.001) [65].…”
Section: Post-myocardial Infarction Patientsmentioning
confidence: 99%